Information Publication Strategy of Pelindo SPMT Belawan from the Perspective of the Journalistic Code of Ethics on Instagram - Muhammad Hasbi Maulana; Abdul Rasyid (Jurnal IPTEK Bagi Masyarakat, 2026)
This study aims to analyze the information publication strategy of Pelindo SPMT Belawan on Instagram from the perspective of the journalistic code of ethics. This study employed a descriptive qualitative approach with data collected through observation, in-depth interviews, and documentation of the Instagram account @pelindospmt_belawan. The informants consisted of internal parties directly involved in managing the company’s social media. Data were analyzed using the Miles and Huberman model through data reduction, data display, and conclusion drawing. The findings show that Pelindo SPMT Belawan implements an information publication strategy that is planned, collaborative, and adaptive to social media trends. The application of journalistic ethics is reflected in information verification processes, content evaluation mechanisms before publication, and the use of language adjusted to public understanding. The study also found challenges related to controlling operational visual content and managing digital information that spreads rapidly on social media. This study indicates that corporate social media not only functions as a medium for company information publication but also requires the implementation of digital communication ethics principles to maintain credibility and public trust.